Integrated Pest Management of Brinjal Fruit and Shoot Borer, Leucinodes orbonalis (Guenee.): Strategies, Emerging Technologies and Meteorological Drivers - Reddy, Nikhil K. S.; Vijay, Anitha; Kalyan, Mude Pavan; Sugeetha, G.; Nagarjuna, T. N.; Suresha, G. V. (International Journal of Bio-resource and Stress Management, 2025)
This review comprehensively evaluated the integrated pest management (IPM) strategies for sustainable control of the brinjal fruit and shoot borer, Leucinodes orbonalis (Guenee), a major constraint to eggplant production across South and Southeast Asia. The study emphasized a multi-tactical framework that integrated biological, cultural, mechanical, chemical, and emerging biotechnological interventions to minimize pest incidence and crop loss. Biological control constituted a cornerstone of IPM, utilizing key parasitoids such as Trathala flavoorbitalis and Trichogramma chilonis, as well as microbial agents including Trichoderma longibrachiatum and entomopathogenic nematodes (Heterorhabditis spp.), which enhanced natural suppression of larval populations. Cultural and mechanical practices-particularly weekly pruning and destruction of infested shoots and fruits, coupled with field sanitation-were essential for disrupting the pest life cycle. Pheromone-based monitoring and mass trapping served as precise tools for surveillance and population reduction, enabling timely and need-based interventions. Chemical control remained an integral component under threshold-based conditions; however, the use of selective insecticides such as Spinosad and Chlorantraniliprole in rotation with biopesticides was recommended to delay resistance and conserve beneficial arthropods. Additionally, transgenic Bt brinjal expressing the Cry1Ac protein provided a highly effective and environmentally compatible option, substantially reducing insecticide dependence. Collectively, the integration of these complementary tactics within an ecologically balanced IPM framework offered a sustainable, cost-effective, and scientifically robust approach for managing L. orbonalis, improving yield stability, and enhancing profitability in eggplant cultivation systems.